Peningkatan Peran Serta Masyarakat dalam Pelaksanaan Pembangunan Daerah - Baswir, Revrisond (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1997)
As national government budget will be more depended upon tax levy, local development finance would virtually be determined by public contribution. The problem of balancing financial allocation between central and local government, therefore, is the problem of shifting peopleÃ¢â¬â¢s fund contribution from central government to the local government. Likewise, by delegating policies to local government for collecting the public fund, people participation in local development finance will be enhanced. It might contrasts to common analysis that there is no significant relationship between local autonomy policy and central-local finance sharing or much analysis which concentrate more on Second Stage Local Governments (Pemda Tingkat II) struggle to increase their local revenue. There are some potential alternatives to improve people participation in local development; First, enhance Local Planning Board (Bappeda Tingkat II) capability to formulate development plans. Overall reformation is needed to development planning mechanisms in each stages of government administration. Second, shift or modify the central-local development finance systems so that there will be more leeway for local government to finance development based on their priorities. Third, give more power to local legislative council (DPRD) to control local executives (Gubernur and Bupati) so that local executives will be responsible much more to the local people rather than to the central government. Conclusively, all efforts to enhance people participation is very closely related to local autonomy improvement and parallel to this is national democracy improvement.